Penerapan ISAK 35 Sebagai Landasan Akuntabilitas Dan Transparansi Keuangan Masjid: Studi pada Masjid Darussalam Krian - Yudhanti, Ashari Lintang; Margarita, Risna Prisilia (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
Accountability and transparency are key principles in the financial management of non-profit organizations, including mosques. As an institution that depends on public funds, mosques have the responsibility to prepare reliable financial reports in accordance with accounting standards. This study aims to analyze the conformity of the financial statements of the Jami' Darussalam Mosque with ISAK 35 and evaluate its accountability and transparency. The research method uses a case study with a qualitative approach, involving in-depth interviews, observation, and document analysis. The results show that financial reporting is still simple, with challenges in the form of limited human resources and understanding of accounting standards. Accountability is not maximized due to the absence of a supervisory system and reward and punishment, while transparency is less than optimal because it is not supported by a legal framework of openness and independent audits. These findings highlight the need to improve the application of ISAK 35 to support more accountable and transparent mosque financial management.